Students’ Perception Toward the Use of Written Test in Learning English by the Fifth Semester Students of English Department of FKIP UKI Toraja - Rachel Rachel (UKI TORAJA, 2017)
The objective of this research is to know the perception about written test inlearning English by the fifth semester students’ of English Department of FKIPUKI Toraja. The research method applied in this research is qualitative descriptivemethod. The subject of this research was the fifth semester students’ in EnglishDepartment at UKI Toraja. To collect data, the writer used interview as aninstrument. Next, data analysis was done through some steps. Those aretranscription, extracting, interpretation, and categorizing. The result of thisresearch showed that there are many perceptions in learning English by the fifthsemester students’ in English Department at UKI Toraja which can be seen in twokinds, they are positive and negative perception. Ten respondents that had beeninterviewed showed that they have different perception. It was found there are 7students’ have positive perceptions and 3 negative perception toward the use ofwritten test in learning English. Based on the research, it can be concluded that thefifth semester students in English Department at UKI Toraja have more positiveperception toward the use of written test in learning English